Cadmium in Chinese coals: Abundance, distribution, occurrence, and environmental effects. Issue 3 (3rd April 2019) - Cheng, Siwei; Liu, Guijian; Liu, Yuan; Wu, Dun
ABSTRACT: Cadmium (Cd) in coals has attracted much attention due to its potential toxicity. In the present study, we reviewed up-to-date information on the abundance, distribution, and modes of occurrence of Cd in Chinese coals, as well as its environmental effects. With the 3110 sets of data rearranged, the arithmetic and weighted mean of Cd concentration in Chinese coals were calculated. Using coal reserves in individual province and coal-forming ages as weighting factors, the estimated average Cd abundances in Chinese coals are 0.25 mg/kg and 0.42 mg/kg, respectively. Variations in Cd coal abundances in different geographical locations, coal-forming ages, and coal ranks are taken into account. The Cd abundances in northern Chinese coals are significantly lower than those in the southern Chinese coals. Sulfides, especially sphalerite, are the most common Cd carriers in coals. As a semi-volatile element, Cd can be partially transformed into a volatilized form during highly thermal process, which could enrich surrounding fly ash. The combination of electrostatic precipitator and flue gas desulphurization is proved to be a better effective method for reducing emissions of Cd. Heavy loadings of Cd in environmental compartments due to anthropogenic activities have posed a great challenge to atmosphere–land–ocean systems.